2019
DOI: 10.1371/journal.pone.0213253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of detector performance in small 6 MV and 6 MV FFF beams using a Versa HD accelerator

Abstract: 1. Background & purposeInvestigate the applicability of a series of detectors in small field dosimetry and the possible differences between their responses to FF and FFF beams. This work extends upon the series of detectors used by other authors to also include metal-oxide-semiconductor field-effect transistors (MOSFETs) detectors and radiochromic film. We also included a later correction of output factors (OFs) recommended by the recently published IAEA´s code of practice TRS 483 on dosimetry of small static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…This study found that ion chambers overestimated the measured penumbra, while EDGE and EBT3 accurately estimated penumbra. These results are in agreement with the data obtained from other published studies [28,[33][34][35][36][37]. The enlarged penumbra observed with ionization chambers was due to a higher range of secondary electrons being present in air than in water and the volume averaging effect.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that ion chambers overestimated the measured penumbra, while EDGE and EBT3 accurately estimated penumbra. These results are in agreement with the data obtained from other published studies [28,[33][34][35][36][37]. The enlarged penumbra observed with ionization chambers was due to a higher range of secondary electrons being present in air than in water and the volume averaging effect.…”
Section: Discussionsupporting
confidence: 92%
“…in 2019 contains OFs for microDiamond measured in a 6 MV beam under equivalent conditions to our measurements, with OFs of 0.518 for the 0.6 cm × 0.6 cm field and 0.794 for 1 cm × 1 cm field. [ 22 ] Our measurements are in agreement with these values. As per TRS-483, the Razor ionization chamber requires larger field output correction factors due to volume averaging as the detector is large relative to field size.…”
Section: Discussionsupporting
confidence: 90%
“…Lechner et al generated stereotactic 3Dconformal plans for brain metastases, as well as VMAT plans for head and neck and prostate cancer patients, and looked at the dosimetric effects of output factor inaccuracies [39]. Monasor Denia et al compared the detector performance in a Versa HD accelerator [40]. Mamballikalam et al evaluated the dosimetric efficacy of VMAT compared to dynamic conformal arc therapy and 3D conformal radiotherapy for very small (<1 cm 3 ) and small (<3 cm 3 ) volume tumours [41].…”
Section: Discussionmentioning
confidence: 99%